Pemanfaatan Sumber Daya Air di Kawasan Percandian Bumiayu, Kabupaten Penukal Abab Lematang Ilir (PALI) - Dian Susilastri; Sondang Martini Siregar; Erlinda Rosita (Badan Riset dan Inovasi Nasional (BRIN), 2022)
The Bumiayu temple area is located in a swamp and is affected by the tides of the Lematang River. The problem in this research concerns the application of local wisdom in aspects of a) the location, b) the types of water resources and c) the benefits of water resources. The objectives of the research are a) to find out the location such as the height and slope of the land, b) to know the types of water resources c) to find out the benefits of resources. The method used in this research is a qualitative method with an explanatory descriptive study of the data. Data were collected through literature observation and field observations. Analysis of the position with morphography, morphometry, and the benefits of features with interview studies. The results showed that the enshrinement area is in the lowlands with an elevation of 0-40 masl and a gentle slope (8% - 13%); water resources consist of surface water resources, namely natural and artificial water resources; the benefits of water resources are for drinking water and practical needs, transportation media, flood control, and ritual media. The Bumiayu people already have local wisdom in choosing temples that are adapted to environmental conditions.